Creating Visual Narrative Art for Decoding Stories that Consumers and Brands Tell - Megehee, C.; Woodside, Arch (John Wiley & Sons, Inc., 2010)
Creating visual narrative art (VNA) of stories that consumers and brands tell achieves several objectives. First, creating VNA revises and deepens sense making of the meaning of events in the story and what the complete story implies about oneself and others. Second, creating VNA surfaces unconscious thinking of the protagonist and other actors in the story as well as the storyteller (recognizing that in many presentations of stories an actor in the story is also the story teller); unconscious thinking in stories relating to consumer and brand experiences reflect one or more archetype (Jung, 1916/1968) fulfillments by the protagonist and the storyteller; given that almost all authors agree on a distinction between processes that are unconscious, rapid, automatic, and high capacity (System 1 processing) and those that are conscious, slow, and deliberative (System 2 processing; see Evans, 2008), VNA enables and enriches processing, particularly relating to System 1 processing—enabling more emotional versus rational processing. Third, creating VNA of stories is inherently and uniquely fulfilling/pleasurable/healing for the artist; using visual media allows artists to express emotions of the protagonist and/or audience member, to vent anger, or to report bliss about events and outcomes that words alone cannot communicate; VNA provides a tangible, emotional, and holistic (gestalt) experience that is uniquely satisfying and does so in a form that many audience members enjoy over and over again. This article elaborates on the rationales for its central proposition, briefly reviews relevant literature on VNA, and illustrates one mode of VNA for the complementary stories told by a consumer and brand.